Study of the vaccination effects against Staphylococcus aureus, causing mastitis and endometritis in cows - E. V. Ivanov; A. V. Kapustin; N. N. Avduevskaya (Ветеринария сегодня)
The high contagiousness of staphylococcal infections and emergence of antimicrobial resistant strains call for search and development of new highly effective drugs and vaccines against infectious animal diseases. Twenty adult pregnant black pied cows were used to form a test and a control groups (10 animals per group). The vaccine was administered twice subcutaneously in the middle third of the neck of the test animals: the first dose in a volume of 3 mL 55–70 days before calving, the second dose in the same volume 25–30 days before the expected calving. Control animals were injected subcutaneously with the same volume of sterile saline at the same dates. To evaluate the antigenicity of the vaccine against Staphylococcus aureus, blood was collected from animals of both groups: in the test group 14–16 days after booster vaccination, in the control group 14–16 days after second injection of the sterile saline. For bacteriological testing, milk samples from both groups were collected during the first month of lactation after calving. According to the results of serological testing, the antibody titer against Staphylococcus aureus in the test group ranged from 4.01 to 4.61 lg, its mean value was (4.34 ± 0.06) lg. In the test group, the mean antibody titers against Staphylococcus aureus were 5.8 times lower and were equal to (0.75 ± 0.09) lg with fluctuations from 0.3 to 1.2 lg. The bacteriological tests of milk in the control group revealed Staphylococcus aureus in 5 out of 10 samples, which is 50%. In the test group, the pathogen was detected in 20% of cases, which is 2.5 times lower than in the control group.